Clinical Learning Environment: Experience of Nursing Students - Thapa, Neelam; Kumar Sharma, Rajesh; Sharma, Rakesh (International Journal of Nursing Research, 2023)
Introduction: The clinical practicum is a large and important component of any nursing degree program. Experiences within clinical context are powerful in shaping student skills and attitudes to learning practice and professional development . Materials and Methods: An exploratory descriptive study was to assess the clinical learning experience of nursing students by selecting 200 nursing students by stratified random sampling technique. Data were collected using self-reporting rating scale tool. Result: Majority (90.5%) of the participants were female and (96.5%) were unmarried. Findings of the study show that majority (90.5%) of students received orientation program before clinical posting, sometimes (76%) staff showed rude attitude to the students and sometimes very unprofessional with the nursing students such as scolding in front of patients and other health care team members, very few (33%) students were agree that articles in the ward were not in hygienic condition, majority (97%) of students agree that they maintained a professional relationship with the nursing staff, and 80.5% were comfortable with physical set-up of ward. Most of (79%) students re-evaluated weekly by nursing faculty, whenever students had stress and anxiety then they resolved it with coping mechanism, sometimes students (62%) found barrier in communication with staff or patient attendant due to some environmental factors. Conclusion: The findings of the study would help to nursing educators to design strategies to create effective clinical learning environment to facilitate better and quality clinical learning for nursing students. Nursing faculties need to be concerned about solving students problems and support them in clinical areas. Faculty of nursing needs to plan clinical rotation in such a way that all nursing students can learn more in clinical setting.